MARCH 2, 1991, EARTHQUAKE (MLH = 7.1) IN THE GULF OF AVACHA, KAMCHATKA, AND ASSOCIATED PHENOMENA - Zobin V.M.; Gordeev E.I.; Levina V.I.; Bakhtiarov F.V.; Guseva E.M.; Droznin D.V.; Ivanova E.I.; Levin V.E.; Petukhin A.G.; Khatkevich Yu.M.; Chirkova V.N. (My University, 1997)
A magnitude MLH = 7.1 earthquake occurred at a distance of 108 km from Petropavlovks-Kamchatskiy City in the early morning of March 3, 1992 local time (12 h 29 min of March 2 GT). Its epicenter was in the Gulf of Avacha 40 km south of Cape Shipunskiy. The event had intensity V-VI at the coast of southeastern Kamchatka and was the largest of the earthquakes that had occurred off southeastern Kamchatka during the past three decades. It was followed by numerous aftershocks. This earthquake was a continuation of the seismic process that started with the October 6, 1987, magnitude 6.6 earthquake in the Gulf of Avacha. It was preceded by an anomalous strain pattern and abnormal variations in several groundwater geochemical parameters. Significantly, some of the geochemical components mimicked the abnormal behavior that had been recorded before the 1987 earthquake, but this time the magnitudes and duration of the anomalies were greater.